Bringing the “Invisible Population” to Light: Justice for Incarcerated and Formerly Incarcerated Women - Cobbina-Dungy, Jennifer E. (Violence against women, 2022)
Women who are involved in the correctional system are often neglected and overlooked. Although justice-involved women enter the carceral system with high levels of abuse and trauma, many are exposed to State violence from staff or incarcerated individuals. Criminal victimization in prison presents a significant threat to one's well-being. According to international human rights law, preventing and combatting violence against women is the responsibility of the State in all contexts, including prisons. It is imperative that women be treated humanely while under the custody of the State, which increases odds of post-release success. Policy implications and recommendations are discussed.